Professional knowledge affects action‐related skills: The development of preservice physics teachers' explaining skills during a field experience. Issue 10 (18th May 2020) - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph
Abstract: Professional knowledge is an important source of science teachers' actions in the classroom (e.g., personal professional content knowledge [pedagogical content knowledge, PCK] is the source of enacted PCK in the refined consensus model [RCM] for PCK). However, the evidence for this claim is ambiguous at best. This study applied a cross‐lagged panel design to examine the relationship between professional knowledge and actions in one particular instructional situation: explaining physics. Pre‐ and post a field experience (one semester), 47 preservice physics teachers from four different universities were tested for their content knowledge (CK), PCK, pedagogical knowledge (PK), and action‐related skills in explaining physics. The study showed that joint professional knowledge (the weighted sum of CK, PCK, and PK scores) at the beginning of the field experience impacted the development of explaining skills during the field experience ( β = .38**). We interpret this as a particular relationship between professional knowledge and science teachers' action‐related skills (enacted PCK): professional knowledge is necessary for the development of explaining skills. That is evidence that personal PCK affects enacted PCK. In addition, field experiences are often supposed to bridge the theory‐practice gap by transforming professional knowledge into instructional practice. Our results suggest that for field experiences to be effective, preservice teachers should start with profound professional knowledge.